The rural community in Belarus after the abolition of serfdom - Maskevich, Anna I. (Journal of the Belarusian State University. History, 2021)
The article explores the creation and the functioning of rural societies in Belarus after the abolition of serfdom. Considerable focus is given to the definition of differences between the terms «rural society» and «peasant community». Territorial differences in the activities of rural societies in Belarus are noted and their formal and informal structure is highlighted. The object of the study is the peasantry of Belarus in the second half of the 19th – early 20th century. The subject of the study is the regularities and features of creation and existence of rural communities in Belarus in the post-reform period. The choice of the object and subject of the study is determined by the importance of peasantry in the population structure and the principal role of peasantry in the processes of social transformation and modernisation in Belarus in the 1860–90s. The goals of the study are to determine the roles and functions of rural society in Belarus after the abolition of serfdom by identifying the differences between the terms «society» and «community»; to investigate the official structure of rural society in Belarus; and to depict the informal influence of society and public opinion on peasant life.
Keywords: peasantry; rural society; peasant community; rural assembly; village headman; public opinion